2022
DOI: 10.1002/nbm.4789
|View full text |Cite
|
Sign up to set email alerts
|

Theory of chemical exchange saturation transfer MRI in the context of different magnetic fields

Abstract: Chemical exchange saturation transfer (CEST) magnetic resonance imaging (MRI) is a versatile MRI method that provides contrast based on the level of molecular and metabolic activity. This contrast arises from indirect measurement of protons in low concentration molecules that are exchanging with the abundant water proton pool. The indirect measurement is based on magnetization transfer of radio frequency (rf)‐prepared magnetization from the small pool to the water pool. The signal can be modeled by the Bloch–M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 72 publications
(139 reference statements)
1
38
0
Order By: Relevance
“…However, another study has shown that APT imaging at 3.5 ppm using B 1,RMS = 1.0 μT performed on two human brains also results in an appropriate APT effect 27 suggesting that the inclusion of saturation with low power (in addition to high power) is still beneficial. Also, the steady‐state optimal B 1 amplitude has been described for a system with a free water pool and a CEST pool 28 . It is a function of the T 1 and T 2 of the free water pool, the solute‐to‐free‐water‐pool exchange rate k s , and frequency offset.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study has shown that APT imaging at 3.5 ppm using B 1,RMS = 1.0 μT performed on two human brains also results in an appropriate APT effect 27 suggesting that the inclusion of saturation with low power (in addition to high power) is still beneficial. Also, the steady‐state optimal B 1 amplitude has been described for a system with a free water pool and a CEST pool 28 . It is a function of the T 1 and T 2 of the free water pool, the solute‐to‐free‐water‐pool exchange rate k s , and frequency offset.…”
Section: Discussionmentioning
confidence: 99%
“…Since this approach is based on the assumption that the water saturation profile is perfectly asymmetric without CEST agents, there are increasing effects to improve the methods of quantifying CEST images. The Web site () and review articles by Zaiss et al , provided in-depth descriptions of CEST theory, mathematical modeling using Bloch-McConnell equations, and quantifying Z-spectral data, along with several examples.…”
Section: Cest Based Molecular Imagingmentioning
confidence: 99%
“…CEST MRI has recently taken center stage due to the rapid development of CEST methodologies 19,20 . A significant advantage of CEST MRI is that it allows for the detection of contrast based on natural metabolites such as amino acids 21 , peptides [22][23][24] , and sugars 25,26 , along with sensitivity to pH [27][28][29] , making it suitable for clinical imaging 30 .…”
Section: -Introductionmentioning
confidence: 99%